Evaluation of a biopsy technique of the epiphyseal plate radius of mules with angular deformity of surgical type: case study - Zambelli Loiacono, Bruno; Martínez Aranzales, José R; Silveira Alves, Geraldo E (Revista Colombiana de Ciencias Pecuarias, 2015)
Summary Background: eight mules with angular limb deformity (ALD) type carpus varus and carpus valgus were studied. Objective: to evaluate a biopsy technique of the distal growth plate of the radius using a Jamshidi needle. Methods: thirteen limbs with ALD were biopsied immediately before undergoing corrective surgery. The site of biopsy depended on the severity of ALD and surgical technique. The samples were preserved and processed for histopathological study. Results: of all biopsies evaluated, only three were successfully obtained. Conclusions: the biopsy technique used was not efficient (23% success rate), however it allowed us to describe the physeal dysplasia in mules with ALD. Our findings agree with those previously described in horses. Keywords: equine, growth plate, periosteal transection and elevation, transphyseal staple, valgus, varus. Resumen Antecedentes: ocho mulares con deformidad angular (ALD) de tipo varus y valgus del carpo fueron estudiados. Objetivo: evaluar una técnica de biopsia para la placa de crecimiento distal del radio con la aguja Jamshidi. Métodos: se utilizaron 13 miembros con ALD; inmediatamente antes de la cirugía correctiva. El lugar de la biopsia varió con la severidad de la ALD y con la técnica quirúrgica. Las muestras fueron conservadas y tratadas para estudio histopatológico. Resultados: se obtuvieron solamente 3 muestras exitosas. Conclusiones: la técnica de biopsia utilizada fue poca eficiente (23%), pero permitió describir la presencia de displasia fisária en mulares con ALD. Los hallazgos coinciden con los descritos para equinos. Palabras clave: equinos, grapa transfisaria, placa de crecimiento, transección y elevación perióstica,valgus, varus. Resumo Antecedentes: oito muares com deformidade angular (ALD) de tipo varus e valgus do carpo foram estudados. Objetivo: avaliar uma técnica de biopsia para a placa de crescimento distal do rádio com a agulha de Jamshidi. Métodos: se utilizaram 13 membros com ALD, imediatamente antes da cirurgia corretiva. O lugar da biopsia dependeu da severidade de ALD e da técnica cirúrgica. As amostras foram conservadas e tratadas para estudo histopatológico. Resultados: três amostras foram obtidas com sucesso. Conclusões: a técnica de biópsia utilizada foi pouca eficiente (23%), mas permitiu descrever displasia fisária em ALD. Osachados concordam com os descritos em equinos. Palavras chave: equino, grampo trans-fisário, placa de crescimento, transecção e elevação de periósteo,valgus, varus.